2004
DOI: 10.1038/modpathol.3800092
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine differentiation in pure type mammary mucinous carcinoma is associated with favorable histologic and immunohistochemical parameters

Abstract: Mucinous carcinoma of the breast is a specific good prognostic type malignancy occurring in elderly patients. Neuroendocrine differentiation has long been described in mucinous carcinoma, but the significance of such finding is uncertain. We evaluated the neuroendocrine differentiation profiles of 38 cases of pure mucinous carcinoma and compared the clinicopathological differences between those with and those without neuroendocrine differentiation. The parameters assessed included patients' age, tumor size, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 9 publications
1
36
1
3
Order By: Relevance
“…[15] However, WT-1 expression was negative in this specimen, arguing against an EMPSGC diagnosis. The described case is unusual in that it exhibits morphologic and immunohistochemical features similar to primary mammary mucinous adenocarcinomas, with neuroendocrine differentiation [16] in its receptor profile and GATA-3 positivity. Studies of chromogranin and synaptophysin are lacking in cases of salivary gland carcinomas, though positivity of neuron-specific enolase and glial fibrillary acid protein has been reported in a mucin-rich salivary gland carcinoma [17].…”
Section: Discussionmentioning
confidence: 97%
“…[15] However, WT-1 expression was negative in this specimen, arguing against an EMPSGC diagnosis. The described case is unusual in that it exhibits morphologic and immunohistochemical features similar to primary mammary mucinous adenocarcinomas, with neuroendocrine differentiation [16] in its receptor profile and GATA-3 positivity. Studies of chromogranin and synaptophysin are lacking in cases of salivary gland carcinomas, though positivity of neuron-specific enolase and glial fibrillary acid protein has been reported in a mucin-rich salivary gland carcinoma [17].…”
Section: Discussionmentioning
confidence: 97%
“…Two previous studies suggested that mucinous carcinoma of breast showing neuroendocrine differentiation had a good prognosis 18,19 . And these groups were characterized by older patient age, and were associated with more favorable histologic and immunohistochemical parameters including lower tumor nuclear grade, lower incidence of axillary lymph node metastasis, and lower cerbB2 oncoprotein expression 18 . In a study regarding mucin-producing sweat gland carcinoma, neuroendocrine differentiation was associated with good prognosis 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A group of human breast carcinomas show histochemical evidence of neuroendocrine differentiation. Neuroendocrine differentiation of mucinous carcinoma of the breast has been reported since 1980, with the tumor being classified as type A (without neuroendocrine differentiation), type B (with neuroendocrine differentiation) and type AB (the intermediate form) 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Esses carcinomas podem apresentar diferenciação neuroendócrina, a qual pode ser avaliada pelo método imunohistoquímico com os marcadores enolase, sinaptofisina e cromogranina (23) . Tse et al classificaram os carcinomas mucinosos em três tipos, conforme grau de diferenciação: A (sem diferenciação), B (com diferenciação) e AB (forma intermediária entre A e B).…”
Section: Carcinoma Mucinoso Da Mamaunclassified